Pengaruh Aturan Berpakaian di Kampus A Terhadap Etika Berbusana Muslim Mahasiswa di Luar Lingkungan Akademik - Zanah, Farhatul; Lestari, Wiwit Yuli (Ta'dib: Jurnal Pendidikan Islam dan Isu-Isu Sosial, 2025)
This study examines the influence of campus dress codes on the dress ethics of Muslim students outside the academic environment. Based on the premise that clothing reflects ethical values, religious teachings, and institutional norms, the research employed a descriptive quantitative method. Data were collected from 36 randomly selected students at a private university in Garut using questionnaires and literature review. Findings reveal that all respondents understand the campus dress code, with 91.7% maintaining Islamic dress principles outside campus. Furthermore, 97.2% acknowledged lecturers as consistent role models in dressing properly, and 94.4% reported parental support in adhering to dress rules. All respondents expressed personal responsibility in upholding their image as Muslim individuals. These results highlight the importance of personal awareness, role models, and family support in internalizing ethical dress habits. The study concludes that consistent dress code enforcement fosters character education aligned with Islamic values both within and beyond campus. It also recommends collaboration between educational institutions and families to strengthen students’ moral and spiritual identity.